Evaluasi produksi limbah tanaman singkong (manihot utilissima) sebagai pakan ternak - Fauzi, Moh Mimbar; Khopsoh, Binti; Afrilia, Tika Fitria Wulan; Lestariningsih, Lestariningsih; Sulaksono, Anang Catur; Anifiatiningrum, Anifiatiningrum (Universitas Islam Negeri Alauddin Makassar, 2025)
The increase in human population followed by land conversion creates its own challenges to provide sufficient feed throughout the year. It is known that cassava waste has the potential as an alternative feed to provide sustainable feed. The treatment in this research includes T1 (leaf), T2 (stem), T1 (cassava peel), and T4 (whole plant), The experimental design used in this study was a Randomized Block Design include 4 treatments and 7 replicated. The best research results on the fresh production aspect are T4 (139,02c± ton/Ha), DM production (85,1c±15,11 ton/Ha), OM production (79,01c± ton/Ha) and CP production (7,89c± 1,40 ton/Ha). Biomass production, whether it is fresh production, organic matter and also crude protein, is shown in T4 (all parts of the plant), but when viewed from the production aspect, the parts of the plant are fresh production, organic matter and also crude protein from the stem